Pengembangan Flipbook “Dukung” tentang Peduli Lingkungan sebagai Media Dakwah pada Pembelajaran PAI Kelas 6 SD - Azkiya, Dzihan; Febrianti, Alisa; Aeni, Ani Nur (ISLAMIKA, 2024)
This research aims to develop a flipbook entitled "SUPPORT" (Da'wah Cares for the Environment) as a medium for da'wah in 6th-grade elementary school Islamic Religious Education (PAI) learning that is effective for conveying environmental care da'wah messages, as well as testing the effectiveness of the flipbook in increasing understanding and a caring attitude towards the importance of caring for the environment in the context of Islamic religious teachings that are appropriate according to the assessment of material experts, media experts and students. The research method used in this development research is Design and Development (D&D), which has a focused objective on the process of designing and developing educational products, analyzing and evaluating these products from a design and development perspective. This research procedure uses the Analyze, Design, Develop, Implement, Evaluate (ADDIE) model, which is a learning development model that is effective, dynamic, and supports ongoing learning. The instruments for collecting this data are observation, material expert validation questionnaire, media expert validation questionnaire, student response questionnaire, and documentation. The results of the research show that the "SUPPORT" flipbook developed is very good and suitable for use in conveying environmental care da'wah messages. The conclusion of this research is that the development of flipbooks as a medium for preaching environmental care in PAI learning for grade 6 elementary schools can make a new contribution to delivering preaching material and environmental education in elementary schools.